Before Taliban : genealogies of the Afghan jihad - Edwards, David B. (University of California Press, 2002)
David B. Edwards traces the lives of three recent Afghan leaders in Afghanistan's history -- Nur Muhammad Taraki, Samiullah Safi, and Qazi Amin Waqad -- to explain how the promise of progress and prosperity that animated Afghanistan in the 1960s crumbled and became the present tragedy of discord, destruction, and despair. Each of the men Edwards profiles were engaged in the political struggles of the country's recent history. They hoped to see Afghanistan become a more just and democratic nation. But their visions for their country were radically different, and in the end, all three failed and were killed or exiled.
Keywords: Safi, Samiullah.; Amin, Qazi Muhammad.; Amin, Qazi Muhammad; Safi, Samiullah; Afghanistan -- History -- Saur Revolution, 1978.; Afghanistan -- History -- Soviet occupation, 1979-1989.; Afghānistān -- Histoire -- 1978 (Coup d'État); Afghānistān -- Histoire -- 1979-1989 (Intervention soviétique); HISTORY.; HISTORY -- General.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Afghanistan; Politiek geweld.; 1978-1989; History